2005
DOI: 10.1007/bf03168450
|View full text |Cite
|
Sign up to set email alerts
|

Toxic effects of cadmium on GABA and taurine content in different brain areas of adult male rats

Abstract: This work assesses the possible changes in gamma amino butyric acid (GABA) and taurine content in the hypothalamus, the median eminence and striatum after the exposure to various doses of cadmium. Cadmium chloride (CdCl2) was administered in the drinking water at the doses of 5, 10, 25, 50 or 100 ppm to adult male rats for 1 month. In the anterior hypothalamus, taurine and GABA content decreased with the dose of 10 ppm of CdCl2 only. Cadmium exposure decreased both GABA and taurine content in mediobasal hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Previous studies demonstrated that the same order of CdCl 2 in drinking water for 2–4 weeks generated apparent damage in the liver (Eşrefoglu et al ., ) and kidneys (Kuliszewski & Nicholls, ; Yurekli et al ., ). In addition, the same order of CdCl 2 in drinking water for 1 month was shown to reduce γ‐amino butyric acid and glutamate content in the hypothalamus and striatum (Caride et al ., ; Lafuente et al ., ), and to cancel circadian variations in dopamine, norepinephrine and serotonin metabolism in the hypothalamus (Lafuente et al ., ). The results of the present study demonstrate that contamination of 100 ppm CdCl 2 in drinking water for only 28 h was sufficient to promote non‐REM sleep and reduce locomotor activities.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that the same order of CdCl 2 in drinking water for 2–4 weeks generated apparent damage in the liver (Eşrefoglu et al ., ) and kidneys (Kuliszewski & Nicholls, ; Yurekli et al ., ). In addition, the same order of CdCl 2 in drinking water for 1 month was shown to reduce γ‐amino butyric acid and glutamate content in the hypothalamus and striatum (Caride et al ., ; Lafuente et al ., ), and to cancel circadian variations in dopamine, norepinephrine and serotonin metabolism in the hypothalamus (Lafuente et al ., ). The results of the present study demonstrate that contamination of 100 ppm CdCl 2 in drinking water for only 28 h was sufficient to promote non‐REM sleep and reduce locomotor activities.…”
Section: Discussionmentioning
confidence: 99%
“…This treatment was not able to induce changes on maternal body weight and it did not induce alterations in pups physical and refl ex developmental landmarks either (Salvatori et al, 2004). In addition, the mean daily dose of Cd given to pups was in the range of those ingested by adult rats chronically exposed to 5-25 ppm (5-25 mg kg ) of Cd in drinking water (Brzóska and Moniuszko-Jakoniuk 2005;Lafuente et al 2005;Rogalska et al 2009). According to Brzóska and MoniuszkoJakoniuk (2005), treatment with this range of doses refl ects real exposure level in moderately to heavily polluted areas, in active tobacco smokers or under occupational exposure conditions.…”
Section: Introductionmentioning
confidence: 94%
“…Cd 2+ was shown to inhibit progesterone synthesis in placental tissues (Kawai et al, 2002). Chronic exposure to Cd leads a disruption of the hypothalamic-pituitary-testicular axis activity in male rats (Iavicola et al, 2009;Pillai and Gupta, 2005;Lafuente et al, 2005) by acting at the hypothalamus level. Thus, it is possible that exposure to Cd during the perinatal period (gestational day, GD, 18-21 and postnatal day, PND, 1-7), a pivotal period of hypothalamictesticular-axis hormone action, could alter some landmarks of pup rats' development.…”
Section: Introductionmentioning
confidence: 97%
“…Aspartate, glutamate, glutamine, GABA and taurine were separated and analyzed using high-performance liquid chromatography (HPLC), with fl uorescence detection after precolumn derivatization with o-phtalaldehyde (OPA), as previously described (Lafuente et al, 2005b(Lafuente et al, , 2007. An aliquot of 20 μl of the tissue supernatant containing homoserine as internal standard was neutralized with OPA reagent (4 mM OPA, 10% methanol, 2.56 mM 2-mercaptoethanol, in 1.6 M potassium borate buff er, pH 9.5) for 1 min.…”
Section: Amino Acids Measurementmentioning
confidence: 99%
“…Experimental studies have dealt with the eff ects of cadmium in synaptic neurotransmission in rat brain (Minami et al, 2001;, brain antioxidant status (increased acetylcholinesterase activity and decreased total antioxidant status) (Carageorgiou et al, 2004), histopathology in developing rat brain (Wong and Klaassen, 1982) and rat neurotransmitter levels (simple sample) in diff erent brain areas such as median eminence, striatum, prefrontal cortex (Esquifi no et al, 2001;Lafuente et al, 2001a), forebrain (Wong et al, 1981) and amygdala (Minami et al, 2001). These include the hypothalamus, which appears to be a target region for this xenobiotic, as it accumulates at this level (Pillai et al, 2003), and it has been shown to induce alterations on aminergic (Das et al, 1993;Lafuente and Esquifi no, 1999;Lafuente et al, 2001b;Pillai et al, 2003) and aminoacidergic (Wong et al, 1981;Minami et al, 2001;Esquifi no et al, 2001;Lafuente et al, 2001aLafuente et al, , 2005b transmitter systems in this same brain area.…”
Section: Introductionmentioning
confidence: 99%